Statistical approach for electrochemical evaluation of the effect of heat treatments on the corrosion resistance of AlSi10Mg alloy by laser powder bed fusion. (10th May 2019) - Cabrini, M.; Lorenzi, S.; Testa, C.; Pastore, T.; Manfredi, D.; Lorusso, M.; Calignano, F.; Fino, P.
Abstract: Laser powder bed fusion (LPBF) is one of the most widespread additive manufacturing (AM) technologies for metals, in which the components are built additively layer upon layer along the z-axis (the building direction) perpendicular to the building platform ( xy-plane ). Here, we evaluated the effect of post-processing heat treatments at 200, 300, and 400 °C on the corrosion resistance of AlSi10Mg alloy manufactured by LPBF for two orientations in the building chamber (XY – parallel to the building plane or XZ – perpendicular to the building plane). Electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization tests were conducted at the constant chloride ion concentration of 0.02 M and 23 °C for the as-built and heat-treated specimens. All specimens were polished on the surface and displayed similar behaviors in the EIS tests. The pitting potential results were widely scattered and therefore analyzed using a statistical approach. Statistical data analysis based on analysis of variance technique (ANOVA) was performed. The results confirmed that the population significantly differs only by considering the heat treatments and the building direction plays only minor role. The cumulative distribution curves of pitting potentials showed a decrease in pitting resistance as the temperature of heat treatment increases. Graphical abstract: Effect of heat treatment temperature on the pitting potentials of AlSi10Mg obtained by means of laser powder bed fusion.Image 1 Highlights: Pitting potentials of AlSi10Mg present a wide experimental variability. Cumulative frequency of pitting potentials shows a deleterious effect of the temperature of post-processing heat treatment. Corrosion attack take place at the edge of melt pool up to 300 °C of heat treatment temperature.